Kegiatan Menulis Kreatif Sastra Pada Siswa Kelas VII SMP Di Jakarta Timur Sebagai Wujud Gerakan Literasi Sekolah - Endang Sulistijani; Arinah Fransori; Friza Youlinda (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
The purpose of writing this paper is to describe creative writing activities for seventh grade students in East Jakarta. This activity was carried out by a team of lecturers, students and alumni of the Indonesian Language Study Program at Indraprasta PGRI University as a form of the Tri Dharma of Higher Education in Community Service. The implementation of this activity lasted for two days at two different schools. The method used in this creative writing activity is the lecture and brainstorming methods. In addition, the Community Service team also used a demonstration method in describing the stages or process of creative writing of literature according to its experience in literary copyright. With literary creative writing activities both writing poetry or short stories, from these our team expected that the more real growth and development of school literacy will occur so that more students produce literary works. Therefore, the outcome of this activity is the publication of Short Story Poetry and Antalogy book by students